Tangles, growth spurts, and being you questions and answers about growing up - Loewen, Nancy 1964-; Mora, Julissa; Skelley, Paula (North Mankato, Minnesota Snap Books, a Capstone imprint, 2015)
"Provides tween-girl-specific information about growing up in a question-answer format"--
Family corner
Includes bibliographical references (page 30) and index
1 2 13 15
NEW_ZTN_GN
Keywords: Child development -- Juvenile literature; Preteens -- Physiology -- Juvenile literature; Preteens -- Social conditions -- Juvenile literature; Puberty -- Juvenile literature; Teenage girls -- Physiology -- Juvenile literature; Teenage girls -- Social conditions -- Juvenile literature